Improved Document Clustering Technique Using K-Mean Method (International Journal of Scientific Research and Management (IJSRM), 2015)
Clustering of document is important for the purpose of document organization, summarization, topic extraction and information retrieval in an efficient way. Initially, clustering is applied for enhancing the information retrieval techniques. Of late, clustering techniques have been applied in the areas which involve browsing the gathered data or in categorizing the outcome provided by the search engines for the reply to the query raised by the users. In this paper, we are providing a methodology for more accurate document clustering. The experimental results have shown that the clustering accuracy cum purity of the proposed technique is better than that of the present clustering technique.